Study of Association of PPH due to Uterine Atonicity and Serum Calcium levels - Parvin, Suraiya; Siddiquee, Nazma (Bangladesh Armed Forces Medical Journal, 2024)
Background: Uterine atonicity stands out as a primary and leading factor contributing to maternal morbidity and mortality. Postpartum hemorrhage (PPH) resulting from uterine atony poses a life-threatening risk. Oxytocic drugs, by elevating intracellular calcium, enhance uterine tonicity, with optimal calcium levels playing a crucial role in facilitating effective uterine contractions. The study aimed to explore the relationship between the concentration of calcium in the bloodstream and the occurrence of PPH associated with inadequate uterine contractions admitted during the 1st and 2nd stages of labour at a tertiary care facility such as the Combined Military Hospital in Dhaka. The study likely involved analyzing data to identify any patterns or connections between serum calcium levels and the incidence of uterine atony-related PPH. Methods: The study follows a randomizing controlled trial (RCT) design within the Department of Obstetrics and Gynecology at Combined Military Hospital, Dhaka. The study duration spans from January 2016 to January 2019, involving a total of 306 subjects. Group A includes those with serum calcium levels between 8-10.4 mg/dl without uterine atonicity, while Group B comprises individuals with serum calcium levels below 8 mg/dl experiencing uterine atonicity, either post cesarean or vaginal delivery. Atonicity features include a soft, distended uterus with a lack of muscle tone. Results: A total of 306 patients were included in the study, with 153 having serum calcium levels exceeding 8 mg/dl and another 153 having levels below 8 mg/dl. Among women with serum calcium levels below 8 mg/dl, 37 patients experienced uterine atonicity. In contrast, it was observed that among women with serum calcium levels exceeding 8 mg/dl, only one patient experienced uterine atonicity. This highlights a potential association between higher serum calcium levels and a reduced likelihood of developing uterine atony in the studied population. Conclusions: The study findings indicate a strong association between low calcium levels and reduced uterine tonicity, establishing low calcium as a significant risk factor for uterine atony. Bangladesh Armed Forces Med J Vol 57 No (1) June 2024, pp 28-34